1996
DOI: 10.1111/j.1532-950x.1996.tb01385.x
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Saphenous Fasciocutaneous Free Flap in Dogs

Abstract: The purpose of this study was to identify the angiosome of the medial saphenous artery and vein and to evaluate the use of this cutaneous angiosome as a free skin flap in the dog. In phase 1 of this study, selective angiography of the medial saphenous artery performed in six canine cadavers showed that the skin covering the entire medial femorotibial area, the distal half of the caudal head of the sartorius muscle, and the gracilis muscle were perfused by the medial saphenous artery. In phase 2, a medial saphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…Our results concur with previously published descriptions of the branching pattern from the saphenous artery. Degner et al noted two cutaneous branches, the more proximal of which coursed caudally and proximally, with the more distal branch extending cranioproximally . This latter branch was identified by Collins and others as the CCSA and was reliably identified in all dogs of our study.…”
Section: Discussionsupporting
confidence: 73%
“…Our results concur with previously published descriptions of the branching pattern from the saphenous artery. Degner et al noted two cutaneous branches, the more proximal of which coursed caudally and proximally, with the more distal branch extending cranioproximally . This latter branch was identified by Collins and others as the CCSA and was reliably identified in all dogs of our study.…”
Section: Discussionsupporting
confidence: 73%
“…Philibert et al, reported seroma formation in four of four dogs following free tissue transfer of the trapezius musculocutaneous flap 15 . Finally, Degner reported seroma formation and partial donor site dehiscence in two of six medial saphenous fasciocutaneous free flaps 19 . In 28 28 comparison to the morbidity associated with tissue harvest from other canine free tissue transfer donor sites, harvesting of the rectus abdominis is associated with minimal morbidity.…”
Section: Phasementioning
confidence: 98%
“…Initially the angiosome of the medial saphenous vasculature was defined through angiography. The medial saphenous fasciocutaneous free flap was then successfully transferred to a forelimb defect in six consecutive research dogs 19 . Medial saphenous fasciocutaneous or myocutaneous free flaps were then successfully transferred in eight clinical cases 20 .…”
mentioning
confidence: 99%
“…A medial saphenous free fasciocutaneous flap 2 was harvested from the medial surface of the right pelvic limb. Its boundaries extended from the distal third of the femur to the proximal third of the tibia and spanned a width of approximately 6 cm.…”
Section: Case Reportmentioning
confidence: 99%
“…Conventional reconstructive techniques often cannot be used for skin loss on the distal aspect of the limbs. Axial pattern skin flaps have been used for proximal antebrachial wounds 1 but are not applicable for repair of distal antebrachial wounds 2 . Skin grafts are not recommended in wound beds with exposed bone, joint, tendon, or those subject to excessive motion.…”
mentioning
confidence: 99%